Operational Modes and Technical Points for Empowering Urban Park Green Spaces by Digital Technology - Yang ZHANG; Changlin LI; Ninglu ZHANG; Fei WU (Fengjing Yuanlin)
ObjectiveAs an important urban public open space, park green spaces bear multiple social functions such as ecology, recreation, and culture. Park services are evolving from being low-frequency and periodic to high-frequency and all-day, giving rise to the urgent need of the public for high-quality and diversified services. However, as a public welfare product, parks have long relied on government financial investment for operation and maintenance, and this traditional operation and maintenance mode exposes deep-seated contradictions of insufficient sustainability under the dual constraints of the downward economic pressure and the rising maintenance costs. This leads to an increasingly prominent contradiction between public demand and operation management. Therefore, against the backdrop of China’s encouragement of the open sharing of urban park green spaces, it is particularly important in the current economic situation to consider how to make better use of digital technologies such as artificial intelligence (AI), Internet of Things (IoT), and big data (BD) to empower the operation of park green spaces, further revitalize the advantageous resources of parks, promote the transformation of parks from “extensive management” to “precise services”, and enhance the “self-sustaining” function of parks through operation. Thus, this research focuses on the operational mode and implementation path of empowering the operation of urban park green spaces by digital technology, with the aim of providing scientific guidance for the future operation practice of park green spaces.Methods/processSpace, scenario, management, and marketing are the four core elements of the operation of park green spaces. Space, as the physical carrier of operation, provides a place for people’s activities in parks; scenario focuses on the feelings and experiences of tourists in parks and is related to tourists’ satisfaction with parks; management covers the cost input of various resources in the operation process and plays a key role in the economic benefits of park operation; marketing involves the online and offline business operation logic of parks and directly affects the commercial revenue and market influence of parks.Results/conclusionTherefore, this research focuses on the above four aspects and divides the operational mode for empowerment by digital technology into the improvement and revitalization of green space, the creation of innovative consumption scenarios, the reduction of operation and maintenance costs and improvement of efficiency, and the improvement of unified revenue and expenditure in marketing. 1) Data-driven improvement and revitalization of space. Through the data-driven mode, accurately identify the inefficiently utilized space and potential demand gaps, and thus formulate targeted transformation strategies to achieve the coordinated improvement of tourists’ needs and space utilization efficiency. 2) Innovative experience in operation scenarios. Digital technology can help reconstruct the logic of scenario experience and consumption mode and. through immersive experience value addition and service efficiency enhancement, activate the integration of the functions and commercial value of park green spaces. 3) Cost reduction and efficiency improvement in operation and maintenance management. Through digital technologies such as AI, Large Language Model, and Big Data, improve the unmanned and automated level of the whole process of environmental event response, resource ledger management, and personnel scheduling to achieve cost reduction and efficiency improvement in park operation. 4) “Online + offline” coordinated management in marketing and operation. Based on data-driven construction of an “online + offline” integrated marketing management mode, through precise reach, business format linkage, and integration of digital platforms, achieve the optimization of tourists’ experience and the improvement of the commercial closed-loop efficiency, ultimately reducing costs and increasing revenue. Based on the above, four specific technical points for implementing the operational mode in reality are proposed as follows. 1) Multi-source data as an auxiliary tool for constructing accurate tourist portraits and optimizing space. Use data to complete the identification of tourists’ needs, diagnosis of inefficient spaces, and optimization and revitalization. 2) Integration of virtuality and reality to promote innovative operation scenarios. Digital technology can realize the immersive experience of integrating virtual and real scenarios, improve the cultural, ecological, and artistic values of parks, make the commercial operation lightweight by means of self-service and upgrading of consumption conversion efficiency, and thus construct a sustainable closed loop of revenue. 3) Construction of a management platform to achieve intelligent operation and maintenance. Through the construction of IoT foundation, data middle platform, and AI-driven platform intelligent agent, achieve intelligent operation and maintenance of parks. 4) Aggregation of traffic and integration of data to enhance operation efficiency. Vertically integrate consumption scenarios in depth, connect court services, equipment rental, and healthy catering support with the sports consumption chain, and connect outdoor science education, natural practice classes, and theme derivatives development with the parent – child consumption chain; besides, horizontally expand cross-domain cooperation, jointly build a ticket intercommunication and point conversion system with surrounding scenic spots and commercial entities, and activate the regional consumption synergy effect.